Changes in trends and pattern of strong opioid prescribing in primary care - Zin, Che Suraya; Chen, Li-Chia; Knaggs, Roger D (European Pain Federation, 2014)
Background: This study evaluated the prescribing trends of four commonly prescribed strong opioids in primary care and explored utilization in non-cancer and cancer users. Methods: This cross-sectional study was conducted from 2000 to 2010 using the UK Clinical Practice Research Datalink. Prescriptions ofbuprenorphine, fentanyl, morphine and oxycodone issued to adult patients were included in this study. Opioid prescriptions issued after patients had cancer medical codes were defined as cancer-related use; otherwise, they were considered non-cancer use. Annual number of prescriptions and patients, defined daily dose (DDD/1000 inhabitants/day) and oral morphine equivalent (OMEQ) dose were measured in repeat cross-sectional estimates.